Exploring customer perceived value change in an UK aerospace manufacturing company: a longitudinal case study - Connor, Paul Brereton (2013)
Organisational members need clearer comprehension about value/s dynamic nature in a constantly changing networked ecosystem of resource integration and mutual service provision. This is so organisational pursuit of competitive advantage for business success is achievable through better stakeholder value propositions which customers especially value in-use. Empirical studies indicate customer perceptions of value are reasonably well documented, however the same cannot be said of knowledge about changes in customer perceived value where the paucity of research reflects its embryonic state.